2021
DOI: 10.3389/fpls.2021.617761
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Mosaics of Fly Pollinators With Divergent Color Preferences Drive Landscape-Scale Structuring of Flower Color in Daisy Communities

Abstract: The striking variation in flower color across and within Angiosperm species is often attributed to divergent selection resulting from geographic mosaics of pollinators with different color preferences. Despite the importance of pollinator mosaics in driving floral divergence, the distributions of pollinators and their color preferences are seldom quantified. The extensive mass-flowering displays of annual daisy species in Namaqualand, South Africa, are characterized by striking color convergence within communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…Such an interaction could result in the observed pattern in which inflorescence color is in contrast to the immediate local environment, whereby darker pigmentation of calyces (i.e., pink) is found in the southern range extent (characterized by bare ground of the Chihuahuan Desert and gypsum outcrops) and lighter calyx pigmentation (i.e., white) provides a strong contrast against the surrounding prairie vegetation in the north. Background substrate color has been shown to impact visibility of flowers of varying colors in bee‐ and fly‐pollinated systems (Bukovac et al, 2017; Ellis et al, 2021), and Crosswhite and Crosswhite (1970) previously hypothesized that the pigmentation of white flowers of C. sessiliflora may serve to increase their visibility to insects under low light conditions in the dry prairies of southern Wisconsin. Experimental assessments of the fitness impact of background contrast are needed to definitively determine the extent to which these factors may explain floral color variation in C. sessiliflora .…”
Section: Discussionmentioning
confidence: 99%
“…Such an interaction could result in the observed pattern in which inflorescence color is in contrast to the immediate local environment, whereby darker pigmentation of calyces (i.e., pink) is found in the southern range extent (characterized by bare ground of the Chihuahuan Desert and gypsum outcrops) and lighter calyx pigmentation (i.e., white) provides a strong contrast against the surrounding prairie vegetation in the north. Background substrate color has been shown to impact visibility of flowers of varying colors in bee‐ and fly‐pollinated systems (Bukovac et al, 2017; Ellis et al, 2021), and Crosswhite and Crosswhite (1970) previously hypothesized that the pigmentation of white flowers of C. sessiliflora may serve to increase their visibility to insects under low light conditions in the dry prairies of southern Wisconsin. Experimental assessments of the fitness impact of background contrast are needed to definitively determine the extent to which these factors may explain floral color variation in C. sessiliflora .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our results thus suggest that the occurrence of competitive or facilitative interactions, even between the same plant species pair, is highly context-dependent. These differential responses might be explained by differences in plant richness among sites (BS: 62, RHA: 47, TP9: 39 plant species; Arceo-GĂłmez et al 2018 ), differences in pollinator assemblages ( Koski et al 2015 ) and/or due to changes in specific pollinator preferences among the study sites ( Ellis et al 2021 ). Geographic variation in the outcome of these interactions can also result from changes in the number and identity of the pollinator assemblage ( GĂłmez et al 2009a ) and plant community composition, as it is also exemplified in studies of diffuse selection (reviewed in Strauss et al 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these backgrounds are different in colour from flowers. Although natural background structures (i.e., leaves, soil, and rocks) are roughly similarly achromatic (Menzel and Shmida, 1993;Ellis et al, 2021), recent studies showed that variation in background colour can determine the salience of flowers to pollinators. Bukovac et al (2017) modelled flower salience against more than 500 natural backgrounds and found that background colour has the potential to significantly change a flower's colour contrast.…”
Section: Do Chromatic and Achromatic Cuesmentioning
confidence: 99%